1974
DOI: 10.1136/adc.49.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Urinary iron excretion in thalassaemia after desferrioxamine administration

Abstract: Seshadri, R., Colebatch, J. H., and Fisher, R. (1974). Archives of Disease in Childhood, 49, 195. Urinary iron excretion in thalassaemia after desferrioxamine administration. Urinary iron excretion induced with desferrioxamine (DFA) was estimated in 26 children with thalassaemia major. Four separate 24-hour urine collections were made-during a baseline period, after intramuscular injection of DFA 1 g, during blood transfusion with DFA 0 5 g/unit transfused blood, and during the post-transfusion period. Urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The 4 patients (Cases 5,7,9,and 10) in whom a marked decrease in the amount of urinary iron was observed had undergone splenectomy 3 to 6 months before retesting. We have previously shown that DFAinduced urinary iron excretion decreases markedly after splenectomy (Seshadri, Colebatch, and Fisher, 1974).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The 4 patients (Cases 5,7,9,and 10) in whom a marked decrease in the amount of urinary iron was observed had undergone splenectomy 3 to 6 months before retesting. We have previously shown that DFAinduced urinary iron excretion decreases markedly after splenectomy (Seshadri, Colebatch, and Fisher, 1974).…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, when assessing the effectiveness of DFA, allowance has to be made for factors such as age, degree of anaemia (Fielding, 1970), and splenectomy (Seshadri et al, 1974) which influence the amount of iron excretion. Our earlier observations on DFA-induced urinary iron excretion suggested that DFA may not be effective in removing the excess iron from the myocardium and liver in the presence of a large spleen (Seshadri et al, 1974).…”
Section: Resultsmentioning
confidence: 99%
“…The successful first application of the chelating drug DF for the removal of iron and the treatment of iron overload in TM became a reality. However, the success was limited and short-lived because of the copious administration procedure and the low efficacy of the daily intramuscular injections of DF initially used [90,91]. A substantial improvement in iron excretion was observed following long-term administration, e.g., 24 h intravenous infusion of DF in comparison to its bolus administration [92,93].…”
Section: [C] Clinical and Biological Effectsmentioning
confidence: 99%
“…All three chelating drugs have exceeded the patent restriction period and are classified as generic pharmaceuticals and belong to the orphan drug category [62]. Deferoxamine has been used parenterally for the treatment of iron-overloading conditions for more than 60 years [89][90][91][92][93][94]. Oral L1 was approved by the regulatory authorities of India in 1995, in Europe and in other countries in 1999 and in the USA in 2011 [112,139].…”
Section: The Aim Of Iron Chelation Therapy In Thalassemia and The Des...mentioning
confidence: 99%